Geographical spread of the invasive species Kellicottia longispina (Kellicott, 1879) and K. bostoniensis (Rousselet, 1908): A scientometric approach - Francieli de Fátima Bomfim; Tatiane Mantovano; Leilane Talita Fatoreto Schwind; Fabiana Palazzo; Claudia Costa Bonecker; Fábio Amodêo Lansac-Tôha (Acta Scientiarum. Biological Sciences, 2016)
Processes related to biological invasion of inland waters have become a major issue due to the increasing number of cases associated with the potential effects of invasions. Kellicottia bostoniensis and K. longispina are rotifer species originating from North America and have become invasive in several continents. In this sense, this study carried out a scientometric analysis to analyze the geographical distribution and identify patterns of occurrence as well as to fill gaps on the knowledge of these species. The survey was based on articles indexed in databases from 1896 to 2014. There is a greater scientific knowledge of these species in the temperate region, and these are present in many different environments. In Brazil, there is a very small number of studies, and no record of K. longispina. Therefore, it is noteworthy the importance of studies on the occurrence and abundance of these species in poorly studied areas, such as subtropical and tropical regions, for a better understanding of their invasive potential, given the potential effects on different communities, which can affect the structure and dynamics of environments.